Assessment of heart valve frame manufactured by laser powder bed fusion (Transactions on Additive Manufacturing Meets Medicine, 2021)
Typically, the frames of replacement heart valves are manufactured by laser cutting. Whilst this method limits the scope for novel concepts are made possible by additive manufacturing. With this in mind, the feasibility of manufacturing heart valve frames by laser powder bed fusion (LPBF) has been investigated based the SAPIEN 3 frame. Using stainless steel powder, this study has demonstrated the feasibility of successfully manufacturing frames with 0.4 mm cross-sectional dimensions. Although geometric accuracy and surface quality need to be improved, a low porosity of 0.5% was achieved and the frames could be successfully crimped and expanded without any breakages.
Keywords: replacement heart valve frame; laser powder bed fusion